Os nomes comerciais em Naranjal-Paraguai - Lucas, Patrícia (2019)
Naming people and places has always aroused people's curiosity. Nobody names a person or place randomly, without any intention or motivation. In this perspective, the main objective of this research is to investigate the trade names (commercial toponyms) found in the city of Naranjal-Paraguay, in order to categorize them, besides verifying the possible influence of the Brazilian colonization on the commercial toponyms of the city and also to reflect on the possible linguistic beliefs and attitudes adopted in the community through the motivations of the toponyms found. Considering the historical and geographic context of the community investigated, the following questions emerged: What are the most recurring toponymic motivations in Naranjal commercial toponyms? What cultural marks were left by the settlers in the commercial appointments of the community? Is it possible to correlate economic, cultural and social aspects with the motivations for choosing the commercial names found in the city? In order to answer these questions and to reach the proposed objectives, the research was anchored in the theoretical assumptions of Onomastics (DICK, 1992; ISQUERDO, 1996; CARVALHINHOS, 2009; SEIDE, 2011, ANDRADE, 2012). In relation to the intersection of toponymic studies with other areas of linguistics, (CALVET,2008; AGUILERA; BUSSE,2008 KARNOPP; VON BORSTEL,2012, among others), of the study on linguistic beliefs and linguistics attitudes (BUSSE; SELLA 2012; BOTASSINI,2015; DALLEASTE; BUSSE 2016) of linguistic landscape (SILVA; SANTOS; JUNG,2016; SOARES, LOMBARDI; SALGADO,2016; DALLA-VECHIA, 2016, TEIZ; SEIDE; LUCAS, 2018). Methodologically the research is guided by the inductive method in consonance with the quantitative and qualitative data analysis. The data were generated through documentary research, exploratory study and field research through which semi - structured interviews were conducted with owners and clients of commercial establishments cataloged in the urban area of the city of Naranjal. The results of the investigation showed that in the community of Naranjal, the linguistic landscape of the city reveals the predominance the names that the honor people, and of the Spanish language in names the establishments, and the presence of the Portuguese language and hybrids names. In addition, the analysis of the interviews pointed out that the Brazilian colonization in the community influences the commercial toponyms and evidenced the presence of linguistic contact between Brazilians and Paraguayans and the belief that the Portuguese language overlaps with Spanish and Guarani in the daily life of the community. The study also revealed the presence of cultural brands from other cultures, especially the North American and the silencing of the Guarani language, one of the official languages of Paraguay.